THE FACTORS ASSOCIATED WITH THE INCIDENCE OF ANEMIA IN PREGNANT WOMEN IN THE SIPAHUTAR PUBLIC HEALTH CENTER - Kasmara, Dwi Pratiwi (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2021)
Many factors can affect maternal mortality, one of which is caused by anemia in pregnancy. Anemia is a medical condition in which the number of red blood cells or hemoglobin is less than normal Anemia can be caused by several factors. There are direct and indirect factors. The direct factors are the adequacy of consumption of blood-added tablets, pregnancy interval, parity, nutritional status, and infectious diseases. The main cause of anemia is a lack of iron intake in food or blood-added tablets. The incidence of anemia is caused by a lack of iron intake. This research uses crossectional design. The population in this study was the mother of the baby in Sipahutar Public Health Center as much as 42 people, and samples used the total sampling. Data analysis using Chi Square test. The results showed no relationship age (0.00), knowledge (0,00) While the parity had no relationship (0.23) with the incidence of anemia. It is hoped that the expectant mothers are expected to spend time visiting the Puskesmas to follow the counseling or health promotion about the impact of anemia in pregnant women so that pregnant women can have good knowledge.